2008
DOI: 10.3748/wjg.14.5032
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of malignant and benign proximal bile duct strictures: The diagnostic dilemma

Abstract: AIM:To identify the criteria for the differentiation of hilar cholangiocarcinoma (HCCA) from benign strictures. METHODS: A total of 68 patients underwent resection of lesions suspicious for HCCA between 1998 and 2006. The results of laboratory investigations, imaging studies and brush cytology were collected. These findings were analyzed to obtain the final diagnosis. RESULTS: Histological examination of the resected specimens confirmed HCCA in 58 patients (85%, group Ⅰ) whereas 10 patients (15%, group Ⅱ) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 37 publications
1
22
1
Order By: Relevance
“…In addition, the differentiation of HCCA from benign lesions that mimic malignancies has proven a difficult diagnostic problem. Several institutional reports have found 10–15% of patients suspected for HCCA to have been misdiagnosed on microscopic examination of the resection specimen 6,7 …”
Section: Introductionmentioning
confidence: 99%
“…In addition, the differentiation of HCCA from benign lesions that mimic malignancies has proven a difficult diagnostic problem. Several institutional reports have found 10–15% of patients suspected for HCCA to have been misdiagnosed on microscopic examination of the resection specimen 6,7 …”
Section: Introductionmentioning
confidence: 99%
“…Notwithstand ing this, a 25% rate of false dia gnosis especially in complicated case of hilar obstruction is significantly high, higher than most would have expected and higher than most would have considered as occasional. In fact, accord ing to the results of a recent large series of patients with hilar strictures, approximately 16% of patients with hilar strictures and a preoperative dia gnosis of HC proved to have a benign dis ease [9,10,[13][14][15][16][17]. This rate of false dia gnosis cannot be overlooked, especially when misdia gnosis leads to unnecessary, high-risk surgical procedures.…”
Section: Introductionmentioning
confidence: 93%
“…On the other hand, these methods can be applied for biliary drainage as well as for material sampling for brush cytology and forceps biopsy or molecular analysis, which may accomplish a definitive dia gnosis. However, both cytology and bio psy have a low sensitivity for HC rang ing between 41 and 50% for brush cytology [16,44], and 53% for forceps bio psy [44], since cancerous tissue is mainly located in the fibrous stroma surround ing the bile ducts [45].…”
Section: Differentiation Between Hc and Benign Biliary Obstruction Wimentioning
confidence: 99%
“…Since Hadjis and colleagues first reported ‘malignant masquerade’ at the hepatic hilum in 1985, several authors have reported the clinical and pathological features of benign hilar strictures operated under the preoperative diagnosis of presumed malignancy. Most of these studies were published more than 10 years ago. Some studies did not report the actual number of patients who underwent resection and others included gallbladder cancer involving the hepatic hilum.…”
Section: Introductionmentioning
confidence: 99%